Validation of cheap Sample Processing Methods and LAMP Assay for COVID-19 Diagnosis - Opoku, Millicent; Aboagye, Elizabeth; Yusif Ismail, Rahmat; Bonney, Joseph Humphrey Kofi; SYLVERKEN, AUGUSTINA; Song, Jinzhao; Akorli, Jewelna (My University, 2024)
Evaluate and validate cheap sample processing methods and Lamp Assays for diagnosis of Covid 19
Keywords: COVID-19; LAMP Assay